Spectrophotometric determination of phosphite in fertilizers in a flow injection system with online sample preparation - Neto, José Anchieta Gomes [UNESP]; Ito, Helenice Akemi [UNESP]; Das Graças Fernandes, Kelly [UNESP]; De Moraes, Mercedes [UNESP]; Cardoso, Arnaldo Alves [UNESP] (My University, 2000)
A flow injection system with online sample preparation is proposed for the determination of phosphite in liquid fertilizers by spectrophotometry. After loop-based injection, phosphite is oxidized by an acidic permanganate solution (1.0 10-2 mol L-1 KMnO4+1.0 mol L-1 H2SO4) in a heated reactor (50 °C). The phosphate generated is then determined by the molybdenum blue method. Influence of flow rates, temperature, and concentration and order of addition of reagents, sample volume, and reactor configuration for the blue complex formation on recorded signals were investigated. The flow system was applied to phosphite determination in commercial samples of liquid fertilizers. The proposed system handles about 80 samples per hour [0.05-0.40% (w/v) H3PO3; R = 0.9998], consuming about 80 μL sample, 1 mg KMnO4, 25 mg (NH4)6Mo7O24, and 10 mg ascorbic acid per determination. Results are precise [relative standard deviation ≤3.5% for 0.1% (w/v) H3PO3, n = 12] and in agreement with those obtained by gravimetry at 95% confidence level.